Prevalence and incidence of systemic lupus erythematosus in Tucumán, Argentina. (November 2020) - Gonzalez Lucero, Luciana; Barbaglia, Ana L; Bellomio, Verónica I; Bertolaccini, Maria C; Machado Escobar, Maximiliano A; Sueldo, Hector R; Yacuzzi, Maria S; Carrizo, Gustavo A; Robles, Norma; Rengel, Silvia; Cristofari, Alexia; Leal, Maria O; et al.
The aim of this study was to determine the prevalence and incidence of Systemic Lupus Erythematosus (SLE) in Tucumán, Argentina. Methods: The study included inpatient and outpatient charts from four public hospitals and private practice rheumatology clinics, all of them members of the Tucumán Rheumatology Society. Patients older than 16 years with diagnosis of SLE between January 2005 and December 2012 were included. Prevalence and annual incidence were calculated as the number of cases per 100.000 inhabitants during the period 2005 to 2012. Results: Three hundred fifty-three patients were identified. The mean age at diagnosis was 30.5 ± 11.7 years, 93.5% women, 83% mestizos. Prevalence was 24.3 cases/100.000 inhabitants (CI 95% 22.6–28.8) and age-adjusted (≥16 years) of 34.9 cases/100.000 inhabitants (CI 95% 32.8–41.1). The annual incidence in 2005 was 1.8 cases/100.000 inhabitants (95% CI 1–2.9) and 2012 of 4.2 cases/100.000 inhabitants (95% CI 2.9–5.8). Mortality was 9.1%, with infections being the most frequent cause (14/32). Conclusion: The prevalence of SLE in the province of Tucumán was 34.9 cases/100.000 inhabitants.